Improving the Curriculum Based on Character - Marsella Desriyarini Gui; Nurain Kiraman; Mutia Karim; Fitriyawati Karim; Muthi Muharam; Adelia Mohamad; Ananda Saburi; Minarti Hasan; Nurain Laraka; Ismail Latif (MultiTech Publisher, 2023)
Creating new curricula, changing and improving old curricula, implementing curricula, and supervising basic education curricula is known as character-based curriculum development. Among these controls are curriculum monitoring and assessment and improvement curriculum based on feedback from various basic curriculum assessments and evaluations within and outside educational institutions.Curriculum development must be based on religious principles, Pancasila, culture and national education goals. Consisting of four pillars, these values are organized into eighteen principles: religious, honest, tolerance, discipline, hard work, creative, independent, democratic, national spirit, love for the country, appreciation for achievement, friendship and communication, love of peace, love reading, environmental care, social care, and responsibility